Lanthanide Coordination Polymers of Mixed Phthalate/Adipate for Ratiometric Temperature Sensing in the Upper-Intermediate Temperature Range - Thammanoon Chuasaard (2018)
© 2018 American Chemical Society. Based on the mixed phthalate (phth 2- ) and adipate (ad 2- ), [Nd 2 (ad)(phth) 2 (H 2 O) 4 ] (I) and [Ln(ad) 0.5 (phth)(H 2 O) 2 ] (Ln = Eu III (II), Gd III (III), Tb III (IV), Dy III (V), Er III (VI), Tm III (VII), 1Eu III :10Tb III (VIII), 3Eu III :10Tb III (IX), and 5Eu III :10Tb III (X)) were synthesized and characterized. Complexes VIII-X show excellent ratiometric temperature sensing behavior in physiological and higher temperature ranges (303-423 K) rendered by the Tb III -to-Eu III energy transfer process. The efficiency of the process as illustrated through the lifetime measurements depends on both the Eu III :Tb III mole ratio and the temperature. The performance of X in terms of relative sensitivity (S r ), temperature resolution, and measurement repeatability were determined, revealing the maximum S r (S m ) of 1.21%·K -1 at 303 K with reliable temperature resolution and excellent repeatability.